Atopy and the gastrointestinal tract – a review of a common association in unexplained gastrointestinal disease. (March 2014) - Walker, Marjorie M; Powell, Nicholas; Talley, Nicholas J
<x xml:space="preserve">Abstract</x> In addition to diseases conventionally associated with atopy there is increasing recognition that atopy is also linked to a spectrum of gastrointestinal (GI) manifestations, including food allergy, primary eosinophilic GI disease, functional gastrointestinal disorders, gluten interactions, gastroesophageal reflux disease and inflammatory bowel disease. These associations may be underpinned by shared genetic susceptibilities, initiation of related immune pathways and common patterns of exposure to environmental cues, including allergen/pathogen encounters and variations in the composition of the intestinal microbiota. Further scrutiny of GI diseases with prominent allergic-type immune responses may yet redefine treatment paradigms for these common and important atopy-associated diseases. Looking forward, interventions by manipulation of the microbiota or host immune responses hold promise, but there is still room for further exploration of this novel field of host susceptibility, host-microbe interactions and atopy-associated GI diseases.